Criminal Liability of Military Members as Perpetrators of Criminal Acts of Abuse Resulting in Death (Decision Study Number: 83-K/PMT-II/Bdg/AD/VII/2024) - Sukardi, Sukardi; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. Assault is a common and easily occurring offense in society. The consequences of such criminal acts are widespread and frequent, with many cases resulting in the victim's death. Therefore, the punishment demanded for perpetrators must truly reflect a sense of justice for the victims. However, what hapens if the perpetrator of an assault resulting in death is a member of the military, an institution under the Indonesian military command structure? The purpose of this study is to examine and analyze the legal construction of criminal liability for military personnel as perpetrators of assault resulting in death, and to investigate the judicial considerations made by judges in sentencing military members convicted of such offenses. This research falls under the category of normative or doctrinal legal research. The term